Exploring the impact of the COVID-19 pandemic on medical learner wellness: a needs assessment for the development of learner wellness interventions - Cherak, Stephana; Brown, Allison; Kachra, Rahim; Makuk, Kira; Sudershan, Sanjana; Paget, Mike; Kassam, Aliya (Canadian Medical Education Journal, 2021)
Background: On March 11, 2020 the World Health Organization declared the novel coronavirus SARS-CoV-2 disease (COVID-19) a global pandemic. We sought to understand impact of COVID-19 on learner wellness at a large tertiary care academic institution to inform the future development of learner wellness interventions during the COVID-19 pandemic. Methods: A cross-sectional, internet-based survey collected quantitative and qualitative data from learners April-June 2020. Descriptive statistics and univariate analyses were reported for quantitative data. Open-ended, qualitative responses were analyzed deductively using thematic analysis. Results: Twenty percent of enrolled learners in that faculty of medicine (540/2741) participated including undergraduate [Bachelor’s] students (25.7%), graduate [science] students (27.5%), undergraduate medical students (22.8%), and postgraduate resident physicians (23.5%). We found that learner wellness across all stages of training was negatively impacted and the ways in which learners were impacted varied as a result of their program's response to the COVID-19 pandemic. Conclusions: Learners in health sciences and medical education report worsening well-being because of the programs and the systems in which they function with the added burden of the COVID-19 pandemic. Future interventions would benefit from a holistic framework of learner wellness while engaging in systems thinking to understand how individuals, programs and respective systems intersect. The importance of acknowledging equity, diversity and inclusion, fostering psychological safety and engaging learners as active participants in their journey during a pandemic and beyond are key elements in developing wellness interventions.